Le droit de l’OHADA dans les États anglophones et ses problématiques linguistiques - Dickerson, Claire Moore (Revue internationale de droit comparé, 2008)
La décision d’un gouvernement d’adopter ou non un nouveau droit dépendra des réalités politiques. Le droit des affaires de l’OHADA, d’inspiration civiliste, est uniforme sur une espace comprenant 16 pays de l’Afrique de l’Ouest et l’Afrique Centrale. Ces pays ne peuvent pas directement influencer la politique interne de leurs voisins, mais ils peuvent modifier le droit de l’OHADA afin de le rendre plus facilement adoptable par leurs voisins habitués à la common law. Sur le fond, les différences entre les deux systèmes dans le domaine du droit des affaires ne sont pas très marquées, car tous les deux ont des aspects déductifs. Néanmoins, il y a des difficultés de traduction. Il y a également des difficultés culturelles, car l’equity qui agit en parallèle avec la common law apporte une flexibilité au système anglo-saxon, tandis que le système civiliste tel que l’OHADA agit par des règles et des structures. La simplicité de celles-ci peut être un avantage, mais afin de faciliter la politique d’une adhésion éventuelle, il serait utile que l’OHADA accepte de retravailler les traductions avec des juristes anglophones et aussi d’adopter certains concepts juridiques d’origine anglo-saxonne.
Keywords: Anglais; Droit OHADA; Langues

Bringing Formal Business Laws to Cameroon’s Informal Sector: Lessons and Cautions from the Tax Law Example - Dickerson, Claire Moore (Washington University Global Studies Law Review, 2014)
A substantial majority of non-agricultural workers in a developing country such as Cameroon engage in legal businesses below the governmental radar, that is, in the informal sector. Because that segment of the Sub-Saharan economy is critical to subsistence within the region, and because the financial crisis has expanded the informal sector in the Global North, developing economies’ experience with the informal sector is of world-wide relevance. Formal business laws do exist in the formal sector; however, trying to move informal-sector workers to the formal sector where these laws already offer some protection can disrupt the entrepreneurs’ ability to sustain themselves, and to contribute to the national economy. A pilot study in five Cameroonian markets is thus of general interest when it reveals that entrepreneurs there do not benefit from formal business laws, which in turn limits their ability to borrow and their willingness to lend. The same study also suggests that tax literature has interesting, non-coercive strategies to improve tax compliance in ways that may be applicable to facilitating the introduction of formal business laws to the informal sector, instead of forcing informal-sector workers into the formal sector. The tax-morale literature recommends deploying strategies of reciprocity, in addition to providing public goods and services—strategies that encourage compliance—instead of using governmental power to extract tax payments. Similarly, tax-based strategies can apply to business laws while informal-sector workers remain in the informal sector, even though the government’s posture vis-à-vis commercial actors is less direct than vis-à-vis taxpayers. The experience of Cameroon’s informal sector with formal tax law thus provides important insights on steps within the government’s control that would not only improve tax compliance, but would also bring formal business laws and their transaction-cost-reducing potential to the informal sector. The pro-business strategy is to apply tax-morale learning, which calls for government authorities to enter into a reciprocal relationship— respectful and communicative—with private parties and to focus on investing in basic infrastructure.

Harmonizing Business Laws in Africa: Ohada Calls the Tune - Dickerson, Claire Moore (Columbia Journal of Transnational Law, 2005)
OHADA (in English, Organization for Harmonization in Africa of Business Laws) is a system of business laws and implementing institutions. Sixteen West African nations adopted this regime in order to increase their attractiveness to foreign investment. Because most of the member states are former French colonies, the OHADA laws are based on the French legal system. Despite certain economists’ recent, well-publicized assertions that any French-based legal system is incompatible with development, other studies challenge those claims and in doing so outline characteristics that a pro-development system of business laws should possess. This Article reviews selected provisions from OHADA’s corporate law and of OHADA’s institutions, revealing that they correspond to those pro-development characteristics. Interviews conducted with legal professionals in Senegal, Côte d’Ivoire, and Cameroon highlight the local perception that the OHADA regime, while still
Keywords: Africa; Claire Moore Dickerson; Harmonizing Business Laws; OHADA; SSRN

The OHADA Common Court of Justice and Arbitration: Exogenous Forces Contributing to Its Influence - Dickerson, Claire Moore (Law and Contemporary Problems, 2016)

OHADA's Proposed Uniform Act on Contract Law: Formal Law for the Informal Sector - Dickerson, Claire Moore (European Journal of Law Reform, 2011)
The draft uniform act on contracts proposed for adoption by the Organization for the Harmonization of Business Laws in Africa ("OHADA") is a combination of continental and common-law concepts. To be effective in parts of the world where the informal sector is particularly important, for example in the 16 West and Central African states where OHADA currently operates, contract law must be particularly attentive to avoiding traps for the unwary. For this reason, enforcing gratuitous contracts may well be defensible, but requiring registration of commercial actors is not. The complexity of two OHADA laws applicable to contracts, however, increases the risk that law and norms will not overlap, creating just such a trap.
Keywords: Comparative law; contracts; norms

Unified Business Laws for Africa: Common Law Perspectives on OHADA - Dickerson, Claire Moore (GMB Publishing Ltd, 2009)